2020
DOI: 10.21776/ub.jam.2020.018.03.18
|View full text |Cite
|
Sign up to set email alerts
|

Transformational Leadership, Organizational Culture, Quality Assurance, and Organizational Performance: Case Study in Islamic Higher Education Institutions (Iheis)

Abstract: This study aims to examine the relationship between transformational leadership, organizational culture, quality assurance, and organizational performance. It also examined the mediating effect of quality assurance in the relationship between transformational leadership and organizational performance, and between organizational culture and organizational performance. The instruments in the form of Google forms were distributed to employees who work in quality assurance units in several public and private Islam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 36 publications
0
5
0
2
Order By: Relevance
“…Bass et al (2007) mentioned this as transformational leadership (TL). As a leadership trait, motivating and promoting rational thinking have significant implications for employees' innovative behavior, resulting in increased cooperation (Hambali and Idris, 2020;Idris and Adi, 2019). Supriyanto et al (2020) stated that TL had a substantial role in predicting OCB.…”
Section: Introductionmentioning
confidence: 99%
“…Bass et al (2007) mentioned this as transformational leadership (TL). As a leadership trait, motivating and promoting rational thinking have significant implications for employees' innovative behavior, resulting in increased cooperation (Hambali and Idris, 2020;Idris and Adi, 2019). Supriyanto et al (2020) stated that TL had a substantial role in predicting OCB.…”
Section: Introductionmentioning
confidence: 99%
“…Employee performance is the achievement and contribution of individual workers that can be measured. It is a concept with complex aspects and is susceptible to the influence of several variables, which include age, gender, employee recognition and job satisfaction (Hambali & Idris, 2020;Supriyanto, Ekowati, Idris, & Iswanto, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Idris [36] found that in higher education of Indonesia, organizational culture positively and significantly influences organizational performance such as level of absorption of the budget, level of income from research grants, level of accreditation, number of student admissions, number of lecturers' research, and community service. In the case of Indonesians Islamic Higher Education Institutions, Hambali and Idris [37] also found that organizational culture highly influences organizational performance. Also, Taye et al [38] confirmed that in one state university in Beijing, organizational culture (environment, mission, leadership, information, strategy, and socialization) strongly influences the individual performance and overall performance of the university.…”
Section: Discussionmentioning
confidence: 96%